2020
DOI: 10.3389/fphy.2020.00037
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Waveguide-Integrated Graphene Photonic Devices for Sensing and Communication Applications

Abstract: Graphene is a two-dimensional material with numerous intriguing optical properties, such that graphene photonic devices have attracted great interest for sensing and communication applications. However, surface-illuminated graphene photonic devices usually suffer from weak light-matter interactions due to the atomic-layer thickness of graphene, seriously limiting the performances of such devices. To tackle this problem, waveguide-integrated graphene photonic devices have been demonstrated since 2010, which off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 61 publications
(73 reference statements)
0
12
0
Order By: Relevance
“…An undoped graphene monolayer has a constant broadband absorption equal to %2.3 171 . It has been shown that the Fermi level of graphene can be tuned by either electrical or chemical dopant beyond half of the photon energy 156,172,173 (Fig 18) which is critical for sensitivity enhancement in a graphene based label-free biosensor. This happens as a result of graphene becoming transparent due to Pauli blocking effect.…”
Section: A Graphene and Graphene Oxide (Gr And Go)mentioning
confidence: 99%
“…An undoped graphene monolayer has a constant broadband absorption equal to %2.3 171 . It has been shown that the Fermi level of graphene can be tuned by either electrical or chemical dopant beyond half of the photon energy 156,172,173 (Fig 18) which is critical for sensitivity enhancement in a graphene based label-free biosensor. This happens as a result of graphene becoming transparent due to Pauli blocking effect.…”
Section: A Graphene and Graphene Oxide (Gr And Go)mentioning
confidence: 99%
“…For instance, monolayer graphene absorbs only 2.3% of incident light in the forward direction. 45,46 Therefore, traditional 2DM-based surface-illuminated PDs are limited in terms of their overall responsivity, which typically require specific methods for their improvement. 47,48 In contrast, 2DM-based WI PDs can maximize the light absorption by extending the interaction length between light and matter.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene integrated photonics is an emerging technology , with disruptive potential arising from the combination of peculiar material properties , of graphene, i.e., the most famous bidimensional (2D) material. Graphene attracted the interest of the photonic research community because of four main features: zero-bandgap for operation (detection and modulation) over an extremely broad spectrum of wavelengths (from visible to far-infrared); efficient tunability of the chemical potential by a field-effect that permits optical absorption and refraction modulation, i.e., amplitude and phase modulation of light; ultrahigh carriers’ mobility, exceeding 100000 cm 2 V –1 s –1 in high quality samples , enabling hundreds of GHz operation , ease of integration on passive integrated photonic platforms as for instance SOI or SiN. , These properties are in their combination very appealing for many photonic applications, from sensing to datacom/telecom . Since the first demonstrations of graphene on integrated photonic waveguides for amplitude modulators , and detectors, a lot of effort has been dedicated to the development of reliable technology processes toward the wafer scale integration of high mobility graphene on integrated photonic platforms. , At the chip level, many devices with improved performance have been demonstrated so far: phase modulators (PMs) up to 10Gb/s based on a single layer of graphene (SLG) on doped silicon (Si) waveguide; electro-absorption modulators (EAMs) featuring up to 50 Gb/s on–off keying (OOK) and 40 GHz electro-optical bandwidth based on two SLG on passive Si waveguide; SLG on Si waveguide photodetectors based on both the bolometric effect and photothermoelectric effect for detection of ≥100 Gb/s …”
Section: Introductionmentioning
confidence: 99%